Combined effect of Bi and Ni elements on the mechanical properties of low-Ag Cu/Sn-0.7Ag-0.5Cu/Cu solder joints. (April 2020) - Kong, Xiangxia; Zhai, Junjun; Sun, Fenglian; Liu, Yang; Zhang, Hao
Abstract: This study investigated the mechanical properties for two types of solder alloy: Sn-0.7Ag-0.5Cu-3.5Bi-0.05Ni (SAC0705BiNi) vs. Sn-0.7Ag-0.5Cu (SAC0705) by using nano-indentation. Two kinds of solder alloy balls with a diameter of 400 μm are soldered to Cu pads on FR-4 substrates, and then formed the ball grid array (BGA) micro solder joints of Cu/SAC0705BiNi/Cu and Cu/SAC0705/Cu. Meanwhile, the combined effect of Bi and Ni elements on the mechanical properties of the bulk of low-Ag Cu/SAC0705/Cu was discussed. Experimental results revealed that the indentation depth and area of the bulk of Cu/SAC0705BiNi/Cu solder joints were smaller than that of Cu/SAC0705/Cu under the same load and strain rate. It was observed that the indentation morphologies of the two kinds of the bulk of micro solder joints have piling-up phenomenon at lower strain rate. Under the maximum load of 20 mN and the strain rate of 2.5 × 10 − 1 s −1, the indentation hardness of the bulk of Cu/SAC0705BiNi/Cu and Cu/SAC0705/Cu solder joints was 0.449 GPa and 0.200 GPa, respectively. And the strain hardening exponent was 0.302 and 0.159, respectively. Additionally, the stress-strain relationship was developed for the bulk of Cu/SAC0705BiNi/Cu and Cu/SAC0705/Cu micro solder joints. Compare with the bulk of the low-Ag Cu/SAC0705/Cu micro solder joints, the indentation hardness, indentation modulus and strain hardening exponent of the bulk of Cu/SAC0705BiNi/Cu achieve an improved by adding Bi and Ni elements. Highlights: The mechanical properties of Cu/SAC0705/Cu micro solder joints were improved by the common addition of Bi and Ni elements. The indentation hardness, modulus, yield stress and stress hardening exponent were determined by nano-indentation method. The stress-strain relationship of Cu/SAC0705BiNi/Cu and Cu/SAC0705/Cu micro solder joints was established, respectively.